Metrolingual multitasking and spatial repertoires: 'Pizza mo two minutes coming'. (April 2014) - Pennycook, Alastair; Otsuji, Emi
<x xml:space="preserve">Abstract</x> Drawing on data from two restaurants in Sydney and Tokyo, this paper describes the ways in which linguistic resources, everyday tasks and social space are intertwined in terms of metrolingual multitasking. Rather than the demolinguistic enumeration of mappable multilingualism or the language‐to‐language or language‐to‐person focus of translingualism, metrolingualism focuses on everyday language practices and their relations to urban space. In order to capture the dynamism of the urban linguistic landscape, this paper explores this relationship between metrolingual multitasking – the ways in which linguistic resources, activities and urban space are bound together – and spatial repertoires – the linguistic resources available in a particular place – arguing that a focus on resources, repertoires, space, place and activity helps us understand how multilingualism from below operates in complex urban places.